PENGARUH SELF-EFFICACY DAN LOCUS OF CONTROL TERHADAP KINERJA KARYAWAN DIVISI REDAKSI PT. SEMARANG INTERMEDIA PERS - Martha Oktavia; Sri Suryoko (Universitas Diponegoro, 2017)
The face of the current era of globalization, the company encouraged theorganization to achieve effective and efficient company. This is necessary so that the company cansurvive in the era of globalization. The role of human resources having a dominant in the activities ofthe company, PT. Semarang Intermedia Pers is a printing press company, based on the existence ofan individual problem, there is an observation that the employees especially in the editorial division. Itcan be a good or bad impact on the employees, and a company's success with employee performancecan be viewed from the decisive goal of the company, for that employees not only have adequatecompetence but also behavior-behavior that shows the great contributions and individualcharacteristics including is self-efficacy and locus of control. The research results show that thevariable self-efficacy and locus is of control in partial have had a positive impact and significantimpact on of employee performance.. Companies are advised to keep improving the performance ofemployees by conducting training for employees to develop their personality with attention to factorsof self-efficacy and locus of control, thereby reducing the problems experienced by the individualemployee and the employee's performance will also be improved.